Interaction of Number Magnitude and Auditory Localization. (January 2016) - Golob, Edward J.; Lewald, Jörg; Jungilligens, Johannes; Getzmann, Stephan
The interplay of perception and memory is very evident when we perceive and then recognize familiar stimuli. Conversely, information in long-term memory may also influence how a stimulus is perceived. Prior work on number cognition in the visual modality has shown that in Western number systems long-term memory for the magnitude of smaller numbers can influence performance involving the left side of space, while larger numbers have an influence toward the right. Here, we investigated in the auditory modality whether a related effect may bias the perception of sound location. Subjects ( n = 28) used a swivel pointer to localize noise bursts presented from various azimuth positions. The noise bursts were preceded by a spoken number (1–9) or, as a nonsemantic control condition, numbers that were played in reverse. The relative constant error in noise localization (forward minus reversed speech) indicated a systematic shift in localization toward more central locations when the number was smaller and toward more peripheral positions when the preceding number magnitude was larger. These findings do not support the traditional left-right number mapping. Instead, the results may reflect an overlap between codes for number magnitude and codes for sound location as implemented by two channel models of sound localization, or possibly a categorical mapping stage of small versus large magnitudes.